Criação de filhos na diversidade: coparentalidade e perspectivas de casais homoafetivos no Brasil - Souza, Lucas Henrique Rimoldi de (Universidade Federal de São Carlos, 2025)
Despite legal advancements, such as the recognition of the right to adoption by same-sex couples in Brazil in 2015, these families experience discrimination and their legitimacy is still subjected to controversy. Considering the limited number of studies on coparenting in this context in the country, the present study aimed to investigate parenting and coparenting experiences in same-sex parent families. A total of 43 parents from same-sex parent families participated in the survey, responding to an online questionnaire that included a sociodemographic section, the 35-item Coparenting Relationship Scale (CRS), and a five-question open-ended questionnaire on parental practices. Results indicate notably positive parental and coparental patterns. The answers to the open-ended questions suggest that participants prioritize love, affection, communication, patience, and an equal division of labor, a finding that corroborates international literature. A recurring challenge, mentioned by 17% of the participants, was prejudice and social stigmatization. The CRS scores confirmed these qualitative findings, with high scores in the positive attitude subscales (e.g., Support = 5.27; Approval = 5.31) and low scores in the negative attitude subscales (e.g., Sabotage = 0.59). The study contributes to the Brazilian literature in the field with evidence that sexual orientation does not negatively affect parenting quality. Our findings reinforce the need to demystify prejudices and support same-sex parent families, who demonstrate being capable of providing healthy environments for the development of their children.
Raising children in diversity: coparenting and same-sex couples' perspectives in Brazil
Keywords: Homoparentalidade; Coparentalidade; Parentalidade; Diversidade familiar; Adoção; Same-sex parents; Parenting; Family diversity; Adoption; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::DESENVOLVIMENTO SOCIAL E DA PERSONALIDADE